A Study on Awareness of RTE Act 2009 among the Parents of Minority Community of Varanasi City - Tripathi, Vivek; Kamath, Asha KVD (JOURNAL OF INDIAN EDUCATION, 2015)
Education is a basic need as well as the right of every child. But when children due to various reasons are not able to enjoy this right, there is a need for an Act to enforce the right. In spite of all efforts, if the Act is to be implemented in its true spirit, it is necessary for the stakeholders to have an awareness of the Act. This study is an attempt to investigate the awareness of Right to Education (RTE Act 2009) among the parents of Minority Community of Varanasi City. The sample consists of 73 Muslim minority parents selected randomly from the rural and urban localities of the Varanasi city. Descriptive survey method was used for the present study. The main objective of the study was to find out the awareness level of minority community parents related to RTE Act 2009. From the results, it was found that there is significant difference in the awareness level of RTE Act among male and female parents; male parents have higher level of awareness on RTE Act than female parents. Another finding was that the parents who send their children to private schools were more aware about the RTE Act than the parents who send their children to government schools. A significant difference was also found in the awareness level of RTE Act among rural and urban minority parents and that the urban parents are more aware of RTE Act than the rural parents.